Theoretical Foundations of The Creation of a Curriculum in Higher Project IT in Education - Glushchenko, Valery V. (Indonesian Journal of Teaching in Science, 2023)
The subject of the work is the formation of theoretical foundations for the creation of curricula in higher project IT education; the object of the work is the curriculum in higher IT education; the purpose of the work is to increase the curriculum in higher project IT education; to achieve this goal, the article solves the following tasks: Descriptions of the essence and structure of the curriculum, the formation of methodological provisions of the theory of curriculum, descriptions, and discussions of the mechanism of curriculum formation in higher project IT education.